Efektivitas Terapi Musik Klasik Dalam Menurunkan Tingkat Kecemasan Pada Pasien Kanker Payudara Yang Menjalani Kemoterapi Pertama - Rustam, Muh Zul Azhri; Suhardiningsih, A.V. Sri; Athiah, Ani Christin (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Objective: The purpose of this study was to determine the effectiveness of classical music therapy in decreasing the anxiety of breast cancer patients undergoing their first chemotherapy.Methods: This research design is Quasi-Experimental with a Pre-Post Test Design. The sample of this research is breast cancer patients who will undergo the first chemotherapy. The sampling technique used was the Non-probability Sampling technique with a Quota Sampling approach.Results: The results obtained in the Wilcoxon Signed Rank Test in the treatment group obtained a significance value (p) = 0.000 smaller than α = 0.05 so that the hypothesis is accepted. There is a significant difference in anxiety before and after intervention in the treatment group. While the results of the Mann Whitney U Test obtained a significance value (p) = 0.000 is smaller than α = 0.05 so that the hypothesis is accepted, there is a significant difference in anxiety between the treatment group and the control group.Conclusion: Classical music therapy can calm the mind and control emotions. Classical music can also help patients as it can distract them from unpleasant events.